2009
DOI: 10.1007/s00384-009-0684-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of large colorectal polyps

Abstract: EP is relatively safe and effective for benign-appearing LCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
17
0
3
Order By: Relevance
“…Perforation has been reported as occurring in 0% to 4% of cases (3,15,18,22) . Caputi et al (5) reported in their series 2.3% of perforation after EMR (all polypoid carcinomas). Swan et al (45) described a target sign as a marker of muscularis propria resection and, therefore, potential perforation during EMR of colorectal lesions, with an incidence of 3.8% for en bloc resection and 1.6% for piecemeal resection (P = 0.16).…”
Section: Discussionmentioning
confidence: 86%
“…Perforation has been reported as occurring in 0% to 4% of cases (3,15,18,22) . Caputi et al (5) reported in their series 2.3% of perforation after EMR (all polypoid carcinomas). Swan et al (45) described a target sign as a marker of muscularis propria resection and, therefore, potential perforation during EMR of colorectal lesions, with an incidence of 3.8% for en bloc resection and 1.6% for piecemeal resection (P = 0.16).…”
Section: Discussionmentioning
confidence: 86%
“…12 Furthermore, one study advocating EMR at colonoscopy for large colorectal polyps reported on a series of 151 polyps undergoing EMR with 3 perforations and 2 cases of copious haemorrhage requiring emergency bowel resection. 13 These are significant incidences for serious complications. EMR at colonoscopy cannot therefore be considered to be a procedure without risk, particularly for large polyps and in situations with difficult access.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The polyps are snared or removed with diathermy, either en bloc or in a piecemeal fashion.…”
mentioning
confidence: 99%
“…Complications of EMR are less frequent than for standard endoscopic polypectomy. [1][2][3][4][5] The most common adverse event is bleeding (which can be immediate or delayed) and significant bleeding occurs in up to 6.1% of patients. 1 Perforation is uncommon, occurring in 4% of patients, and is suspected in patients complaining of severe abdominal pain not relieved by passing flatus.…”
mentioning
confidence: 99%
See 1 more Smart Citation